Biomedical Engineering 2017
DOI: 10.2316/p.2017.852-053
|View full text |Cite
|
Sign up to set email alerts
|

Skin Lesion Classification from Dermoscopic Images Using Deep Learning Techniques

Abstract: The recent emergence of deep learning methods for medical image analysis has enabled the development of intelligent medical imaging-based diagnosis systems that can assist the human expert in making better decisions about a patients health. In this paper we focus on the problem of skin lesion classification, particularly early melanoma detection, and present a deep-learning based approach to solve the problem of classifying a dermoscopic image containing a skin lesion as malignant or benign. The proposed solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(64 citation statements)
references
References 9 publications
0
44
0
4
Order By: Relevance
“…This is the reason why this model was considered to perform the learning transfer. Lesion recognition systems using learning transfer have been described in the literature with the AlexNet [11], VGGNet [13,14], and ResNet [12,[15][16][17][18] network models, whose performance is similar to the model used for this work.…”
Section: Discussionmentioning
confidence: 99%
“…This is the reason why this model was considered to perform the learning transfer. Lesion recognition systems using learning transfer have been described in the literature with the AlexNet [11], VGGNet [13,14], and ResNet [12,[15][16][17][18] network models, whose performance is similar to the model used for this work.…”
Section: Discussionmentioning
confidence: 99%
“…The CNN achieved an overall AUC of [ 91%, which was similar to the average output predications of 21 dermatologists. Many studies since then have leveraged transfer learning to classify lesions into a number of skin cancer classes and determine the probability of malignancy; these studies showed comparable accuracy, AUROC, sensitivity, and/or specificity to board-certified dermatologists or dermatologists in training [19,[31][32][33][34][35][36][37][38][39]. It is also important to note the average dermatologist's diagnostic accuracy (e.g., sensitivity and specificity) when evaluating ML models for general screening.…”
Section: Melanomamentioning
confidence: 99%
“…Neural networks different models modifications are increasingly common. They contain deep learning algorithms [13], deep convolutional neural networks (VGGNet convolutional neural network architecture and the transfer learning paradigm) [28], synergic deep learning (SDL). They show great effectiveness in the diagnosis of skin lesions.…”
Section: Classifiers Based On Deep Convolutional Neural Network (Dcnn)mentioning
confidence: 99%